2009
DOI: 10.1038/jp.2008.237
|View full text |Cite
|
Sign up to set email alerts
|

Hospitalized late preterm mild preeclamptic patients with mature lung testing: what are the risks of delivery?

Abstract: Objective: To evaluate the risk of elective delivery of hospitalized patients with isolated mild preeclampsia with mature fetal lung profile compared with a cohort of patients who had preeclampsia with indicated delivery matched for gestational age.Study Design: Patients with mild preeclampsia requiring hospitalization between 34 and 37 weeks estimated gestational age were offered amniocentesis for assessment of fetal lung maturity. If fetal lung maturity was documented, patients were offered delivery. These c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 16 publications
0
4
0
1
Order By: Relevance
“…16 In one study of late preterm infants, 34–37 weeks’ gestation, who were born to hospitalized women with mild preeclampsia after positive fetal lung maturity testing, 10% of the infants had RDS. 17 Clearly, the continued occurrence of RDS, despite documented fetal lung maturity, indicates that substantial opportunity still exists for improved fetal lung maturity testing.…”
Section: Commentsmentioning
confidence: 99%
“…16 In one study of late preterm infants, 34–37 weeks’ gestation, who were born to hospitalized women with mild preeclampsia after positive fetal lung maturity testing, 10% of the infants had RDS. 17 Clearly, the continued occurrence of RDS, despite documented fetal lung maturity, indicates that substantial opportunity still exists for improved fetal lung maturity testing.…”
Section: Commentsmentioning
confidence: 99%
“…98 The significance of FLM testing in the LP period is questionable as other studies have found higher rates of RDS among infants born after testing mature. [99][100][101] A summary of studies that evaluated the effect of ACS in late preterm infants is presented in ►Table 2.…”
Section: Antenatal Corticosteroid In Late Preterm and Term Infantsmentioning
confidence: 99%
“…With the retirement of the most popular fetal lung maturity test, the FLM-TDx II (the test used in this study), the current methods of fetal lung maturity testing are imperfect in their prediction of respiratory morbidity. Several studies have shown that despite mature fetal lung indices, infants continue to have other respiratory and neonatal morbidities related to prematurity 1. Thus amniocentesis for this purpose is being performed with less frequency.…”
Section: Commentarymentioning
confidence: 99%